PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DITOKO VELG BAN TKB GROUP INDONESIA - Isnaini Putri Rangkuti; Yayuk Yuliana (Journal of Innovation Research and Knowledge, 2021)
The objective of the research was to determine the influence of service quality on customer satisfaction at the Tkb Group Indonesia Medan tire wheel shop.This type of research is quantitative. The population in this study were consumers of the Tkb Group Indonesia Medan tire wheel shop, with a sample of 77 respondents. Sampling using the Slovin method. The data collection technique was done by using a questionnaire, the data analysis was done by using a simple linear regression analysis technique. The results of this study indicate that there is a positive and significant influence between service quality and customer satisfaction at the Tkb Group Indonesia Medan Wheel Tire shop. Where the t test value is 8.405 and the coefficient of determination (R2) is 0.485, this value means 48.5%, meaning that service quality has an influence of 48. The result means that the effect given is positive which for if the quality of service is improved for the better it will affect customer satisfaction to increase, and vice versa.